Land-based pollution and integrated coastal management. - DAHL, Arthur Lyon (1993)
Encourages follow-up initiatives to Agenda 21 to deal with the issues of land-based pollution of the marine environment in an integrated manner, and recommends a number of measures for doing so. Discusses how this will require new institutional approaches capable of fostering cooperation among a government's sectoral agencies, between national and local authorities, and with non-governmental agencies. Highlights the opportunity for island developing nations to set the pace for integrated national sustainable development and to help develop models for larger nations.